Analisis Potensi dan Dinamika Sektor Ekonomi Daerah Menggunakan Pendekatan LQ, DLQ, dan Shift Share di Kabupaten Bojonegoro, Provinsi Jawa Timur - Selvia Dwi. S.; Dwi Rahmawati; Sahra Dwi. I.R; Fahrizal. T (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Regional economic development requires a comprehensive understanding of the structure, potential, and dynamics of economic sectors so that formulated policies can be targeted and sustainable. Bojonegoro Regency as one of the regions in East Java Province has unique economic characteristics with the dominance of certain sectors, so it is necessary to conduct an in-depth analysis of the economic sectors that play a role in driving regional growth. This study aims to identify basic and non-basic sectors, analyze the dynamics of changes in economic sectors, and assess the sectoral competitiveness of Bojonegoro Regency compared to East Java Province. This study uses a quantitative approach with secondary data in the form of Gross Regional Domestic Product at constant prices by business field obtained from the Central Statistics Agency. The analytical methods used include Location Quotient, Dynamic Location Quotient, and Shift Share. The results show that the mining and quarrying sector remains the sector with the most dominant relative advantage in the economic structure of Bojonegoro Regency. However, the analysis of dynamics and competitiveness indicates that several non-extractive sectors are starting to show faster development and growth potential. This finding suggests an opportunity for transformation of the regional economic structure towards a more diverse pattern. The implications of this research emphasize the importance of regional economic development strategies that do not only rely on traditional leading sectors, but also encourage the development of more sustainable potential sectors.